Correlates of serum resistin in elderly, non-diabetic patients with chronic kidney disease. - Marouga, Anna; Dalamaga, Maria; Kastania, Anastasia N; Antonakos, George; Thrasyvoulides, Apollon; Kontelia, Georgia; Dimas, Claire; Vlahakos, Demetrios V (Clin Lab, 2013)
BACKGROUND: Renal function may be a major determinant of resistin levels, since most studies revealed association between elevated resistin levels and decreased glomerular filtration rate (GFR) in patients with chronic kidney disease (CKD). The aim of the present study was to test the hypothesis whether serum resistin is associated with markers of malnutrition and inflammation in elderly non-diabetic adults in different stages of CKD including hemodialysis. METHODS: This was a cross-sectional study of 80 elderly patients divided in four groups of 20 patients each according to eGFR and matched for age (+/- 5 years) and gender. Patients with eGFR more than 1.5 mL/second served as controls. Multivariate regression was used to evaluate the association of resistin with eGFR, demographic, metabolic and inflammatory markers, and insulin resistance. Hematological, biochemical, and immunochemical analyses were performed using commercially available enzyme immunoassays. RESULTS: Our results showed that: 1) serum resistin levels were two times higher in patients with advanced CKD especially those undergoing hemodialysis compared to controls, 2) in univariate analysis, resistin levels correlated directly with Tumor Necrosis Factor-alpha (TNF-alpha), high sensitive C-Reactive Protein (hsCRP), and serum phosphate and inversely correlated with albumin, eGFR, and hematocrit levels. We failed to reveal any relationship between resistin levels and Homeostasis Model Assessment Score of Insulin Resistance (HOMA-IR), body mass index (BMI), cholesterol and leptin levels, 3) in multivariate analysis, only TNF-alpha (p < 0.001) and hsCRP (p = 0.032) were the most important independent determinants of serum resistin levels. CONCLUSIONS: These results indicate that resistin increases as GFR declines and may be involved in the malnutrition-inflammation state and the reverse epidemiology phenomenon present in elderly, non-diabetic patients with CKD.
Keywords: Aged; C-Reactive Protein; Case-Control Studies; Cross-Sectional Studies; Diabetes Mellitus; Female; Glomerular Filtration Rate; Humans; Immunoenzyme Techniques; Kidney Failure, Chronic; Male; Phosphates; Renal Dialysis; Resistin; Tumor Necrosis Factor-alpha